2006
DOI: 10.1016/j.febslet.2006.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of albebetin oligomers depends on cross‐β‐sheet formation

Abstract: Prefibrillar cytotoxicity was suggested as a common amyloid characteristic. We showed two types of albebetin prefibrillar oligomers are formed during incubation at pH 7.3. Initial round-shaped oligomers consist of 10-15 molecules determined by atomic force microscopy, do not bind thioflavin-T and do not affect viability of granular neurons and SH-SY5Y cells. They are converted into ca. 30-40-mers possessing cross-b-sheet and reducing viability of neuronal cells. Neither monomers nor fibrils possess cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…5b), but enlarged round-shaped oligomers with a height of ca 1.0-2.0 nm remained as the dominant species; their dimensions indicate that these oligomers are from octamers to ecosinomers. 36,37 After 7 days of incubation, the quantity of fibrils increased, which were significantly thicker and up to 5-6 nm in height in the AFM cross-sections, but a micrometer in length or shorter (Fig. 5c, c1).…”
Section: Afm Imaging Of α-Syn Amyloidsmentioning
confidence: 90%
“…5b), but enlarged round-shaped oligomers with a height of ca 1.0-2.0 nm remained as the dominant species; their dimensions indicate that these oligomers are from octamers to ecosinomers. 36,37 After 7 days of incubation, the quantity of fibrils increased, which were significantly thicker and up to 5-6 nm in height in the AFM cross-sections, but a micrometer in length or shorter (Fig. 5c, c1).…”
Section: Afm Imaging Of α-Syn Amyloidsmentioning
confidence: 90%
“…Amyloid fibrils have been demonstrated to assemble typically via nucleation and growth kinetics, characterized by an initial lag phase before fibril elongation (8). A wealth of data indicates that species formed during this phase of the reaction are cytotoxic, and, furthermore, that soluble, oligomeric precursors to amyloid fibrils likely represent the critical pathological species in some amyloid disorders (7,(9)(10)(11)(12)(13). Probing the initial stages of the assembly process is, however, challenging because of the low populations of heterogeneous, unstable oligomeric species.…”
mentioning
confidence: 99%
“…Experimental evidence indicates that early aggregates such as the soluble oligomers and protofilaments have a critical role in promoting pathological effects in disorders (Small et al, 2001;Caughey and Lansbury, 2003;Zamotin et al, 2006). Although the cytotoxic nature of the protofilaments remains unclear, they may interact with cell membranes and trigger responses that ultimately lead to cell death, such as oxidative stress (Turnbull et al, 2003) and the increase in free Ca 2þ levels.…”
Section: Protein Aggregationprotofilaments and Oligomersmentioning
confidence: 97%
“…Pastor et al (2008) suggest that the amyloid prefibrillar aggregates exert their cytotoxic effect through a common cell death mechanism related to a particular quaternary structure regardless of polypeptide sequence, length and amino acid chirality. Zamotin et al (2006) in a separate study saw no cell death until characteristic ThT fluorescence indicates b-sheet formation. It has been suggested that nearly all proteins have the ability to form amyloid fibrils under certain conditions, which in itself has implications for understanding protein folding.…”
Section: Toxicitymentioning
confidence: 97%